2015
DOI: 10.1074/jbc.m114.629550
|View full text |Cite|
|
Sign up to set email alerts
|

Site-directed Mutagenesis Reveals Regions Implicated in the Stability and Fiber Formation of Human λ3r Light Chains

Abstract: Background: 6a and 3r are the most implicated germ lines in light chain amyloidosis. Results: Mutagenesis at N-terminal, loop 40 -60, and CDR3 regions affected 3r fibrillogenesis. Conclusion: Changes at residues 7, 48, and 91 increased fibril formation while changes at residues 8 and 40 reverted fibrillogenesis. Significance: Characterization of light chain germ lines helps to identify key regions implicated in amyloidosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 55 publications
0
11
0
Order By: Relevance
“…To date, most studies dealing with the biophysical and structural properties of amyloidogenic LCs have focused specifically on V L domains, as they are abundant in fibrils: typically, V L domains belonging to amyloidogenic LCs are thermodynamically and kinetically unstable, while the three-dimensional structures of amyloidogenic and non-amyloidogenic V L studied match closely 11 15 . However, many observations stress the relevance of studying full length LCs: (i) although V L are abundant in fibrils, the full length LCs and C L domains have also been found in deposits 12 , 16 18 ; (ii) so far, FL LCs and not truncated forms, have been found soluble in blood and serum 19 ; iii) recent reports underline the relevance of the C L domain in determining both the biophysical properties and the aggregation propensity of LCs 20 23 .…”
Section: Introductionmentioning
confidence: 99%
“…To date, most studies dealing with the biophysical and structural properties of amyloidogenic LCs have focused specifically on V L domains, as they are abundant in fibrils: typically, V L domains belonging to amyloidogenic LCs are thermodynamically and kinetically unstable, while the three-dimensional structures of amyloidogenic and non-amyloidogenic V L studied match closely 11 15 . However, many observations stress the relevance of studying full length LCs: (i) although V L are abundant in fibrils, the full length LCs and C L domains have also been found in deposits 12 , 16 18 ; (ii) so far, FL LCs and not truncated forms, have been found soluble in blood and serum 19 ; iii) recent reports underline the relevance of the C L domain in determining both the biophysical properties and the aggregation propensity of LCs 20 23 .…”
Section: Introductionmentioning
confidence: 99%
“…In general, healthy individuals have a kappa to lambda ratio of two to one while AL patients have a kappa to lambda ratio of one to three [3], with a majority of the lambda light chains coming from only a few possible germ lines, such as 3r and/or 6a [8]. Particularly, a mutation of Arg to Gly in position 24 for germ-line 6a has been found in 25% of AL patient samples.…”
Section: Introductionmentioning
confidence: 99%
“…Although germ lines can be identified as kappa (j) or lambda (k) with expression levels in humans of 60% and 40%, respectively [9], it is striking that k V L s encoded by germ lines 6a and 3r are highly susceptible to amyloid aggregation [10]. In order to elucidate the propensity of k6a to amyloid aggregation, a recombinant model light chain encoded by germ line 6a and JL2 gene segments and denominated 6aJL2 was constructed [11,12]. In vitro experiments revealed that the protein product, 6aJL2, showed a thermodynamic stability of 5.2 kcalÁmol À1 , higher than that of other amyloidogenic V L s derived from this germ line.…”
Section: Introductionmentioning
confidence: 99%